Abuse of dominance and antitrust enforcement in the German electricity market - Tomaso Duso; Florian Szücs; Veit Böckers (Energy Economics, 2020)
In 2008, the European Commission investigated E.ON, a large and vertically integrated electricity company, for the alleged abuse of a joint dominant position by strategically withholding generation capacity in the German wholesale electricity market. The case was settled after E.ON agreed to divest 5 GW generation capacity as well as its extra-high voltage network. We analyze the effect of these divestitures on wholesale electricity prices. Our identification strategy is based on the observation that energy suppliers have more market power during peak periods when demand is high. Therefore, a decrease in market power should lead to convergence between peak and off-peak prices, after controlling for different demand and supply conditions as well as the change in generation mix due to the expansion of renewable technologies. Using daily electricity prices for the 2006–2012 period, we find economically and statistically significant convergence effects after the settlement of the case. In a richer specification, we show that the price reductions appear to be mostly due to the divestiture of gas and coal plants, which is consistent with merit-order considerations. Additional cross-country analyses support our results.
Keywords: K21; L41; L94; 330; Electricity; Wholesale prices; EU Commission; Abuse of dominance; ex post evaluation; E.on